Membangun karakter remaja: Pendidikan moral sebagai kebutuhan dalam pencegahan bullying di SMP Negeri 4 Salatiga - Sari Famularsih; Elka Melviyana; Juzan Juzan; Binti Muflikah; Alfin Rosyida (Tintamas: Jurnal Pengabdian Indonesia Emas, 2026)
Bullying is a serious issue in schools that negatively affects students’ psychological Bullying is a serious problem in the school environment that impacts the psychological and social development of students. Based on the results of initial observations at SMP Negeri 4 Salatiga, it was found that students' understanding of bullying is still limited, moral awareness is relatively low, and the use of gadgets is not balanced with good digital ethics, thus potentially triggering bullying behavior. Therefore, this community service activity aims to provide a solution by strengthening students' moral education in the form of educational seminars. The method used is a participatory and educational approach through interactive lectures, discussions, and case studies, involving students as the main participants, teachers as facilitators, and lecturers and students of the MBKM Teaching Assistance Program as activity implementers. The results of the activity showed an increase in students' understanding of the concept and impact of bullying, as well as a growing moral awareness reflected in attitudes of empathy, tolerance, responsibility, and ethical interactions, both in person and through digital media. This activity also has an impact on creating a safer and more harmonious school environment, so it can be concluded that moral education through seminars is effective as an effort to prevent bullying and build adolescent character.